The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fsoil.2022.960426
|View full text |Cite
|
Sign up to set email alerts
|

25 years of continuous sewage sludge application vs. mineral fertilizers on a calcareous soil affected pH but not soil carbonates

Abstract: Inorganic and organic fertilizers have been widely used to maintain crop yields. However, several studies have demonstrated that the dissolution of carbonates in agricultural soils by the acidification induced by N-fertilizers can result in their total or partial loss in the tilled layer of some agricultural soils. The effect of inorganic and organic fertilization on carbonates in calcareous semiarid Mediterranean soils has been less studied and is still unclear. Based on a 25-year field experiment, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…However, the duration of sludge's liming effect on soils can vary, depending on frequency and rate of sewage sludge application, soil properties, cultivated crops and agricultural management practices. The fact that the pH of alkaline soil treatments with sludge remained also unchanged after the experiment is consistent with the findings of De Soto et al (2022), who reported that even a continuous application of sewage sludge (25 years) to an alkaline soil did not cause major changes to its pH because of the CaCO 3 buffering capacity.…”
Section: Discussionsupporting
confidence: 91%
“…However, the duration of sludge's liming effect on soils can vary, depending on frequency and rate of sewage sludge application, soil properties, cultivated crops and agricultural management practices. The fact that the pH of alkaline soil treatments with sludge remained also unchanged after the experiment is consistent with the findings of De Soto et al (2022), who reported that even a continuous application of sewage sludge (25 years) to an alkaline soil did not cause major changes to its pH because of the CaCO 3 buffering capacity.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the high concentration of carbonates in the study soil (21.6%), changes in the carbonate concentration of the bulk samples were not detected. Similar results have recently been observed by de Soto et al [45] after 25 years of continuous sludge and mineral fertilizer application on a Mediterranean calcareous soil. This suggests that the initial carbonate content is a key factor for observing and detecting these changes in bulk soil samples with a high content of carbonates.…”
Section: Carbonate Content Valuessupporting
confidence: 90%